2003
DOI: 10.3136/nskkk.50.457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Royal Jelly Treated with Protease on Blood Pressure in Spontaneously Hypertensive Rats

Abstract: Protease digested royal jelly (ProRJ) proved to inhibit angiotensin I converting enzyme (ACE) activity in vitro.And we have demonstrated that peptides isolated from ProRJ (Ile-Tyr (IY), Val-Tyr (VY)) also inhibited ACE activity.We examined an antihypertensive effect of RJ, ProRJ and RJ peptides (IY and VY) on spontaneously hypertensive rat (SHR). In chronic oral administration of ProRJ and RJ at the dose of 10 mg/kg/day for 28 days, the systolic blood pressure (SBP) of SHR was significantly decreased against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We have shown that Protease N treated RJ (ProRJ) and peptides (IY, VY, IVY) from ProRJ inhibited angiotensin I-converting enzyme (ACE) activity 6) and they have an antihypertensive effect in repeated oral administration for 28 d on spontaneously hypertensive rats (SHR). 7) Their ACE inhibitory activity (IC 50 ) of IY, VY and IVY are 0.008, 0.020 and 0.018 (mg/ml) respectively. 5) Generally, the Renin-angiotensin (RA) system is well known to regulate blood pressure (BP) in the circulatory system and localized organs.…”
mentioning
confidence: 99%
“…We have shown that Protease N treated RJ (ProRJ) and peptides (IY, VY, IVY) from ProRJ inhibited angiotensin I-converting enzyme (ACE) activity 6) and they have an antihypertensive effect in repeated oral administration for 28 d on spontaneously hypertensive rats (SHR). 7) Their ACE inhibitory activity (IC 50 ) of IY, VY and IVY are 0.008, 0.020 and 0.018 (mg/ml) respectively. 5) Generally, the Renin-angiotensin (RA) system is well known to regulate blood pressure (BP) in the circulatory system and localized organs.…”
mentioning
confidence: 99%
“…In this present study, no PPT was apparent in the aboveground parts of Tienchi ginseng. There have been many reports describing hypotensive effect of various food material, [9][10][11][12][13] but they are considered to be expensive and sometimes need special processing to y To whom correspondence should be addressed. Tel: +81-54-264-5526; Fax: +81-54-264-5528; E-mail: riceball 2@ybb.ne.jp Abbreviations: SHRSP, stroke-prone spontaneously hypertensive rat; WKY, Wistar Kyoto rat; PPD, 20(s)-protopanaxadiol; PPT, 20(s)-protopanaxatriol; GABA, -aminobutyric acid; SBP, systolic blood pressure; DBP, diastolic blood pressure; HR, heart rate; LAT, locomotive activity prepare the product.…”
mentioning
confidence: 99%